ANALISIS FAKTOR – FAKTOR PENYEBAB KEGAGALAN PADA PENCAPAIAN TARGET KINERJA (Studi pada PT. Kereta Api Indonesia (Persero) di DAOP 1, DAOP 4, dan DAOP 6) - Rahmana, Yurido Fajar; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze factors that affected the cause of failure in the achievement of performance target goals at PT. Kereta Api Indonesia (Persero). This study used 20 indicators that will be reduced by using factor analysis and continued with adding 1 dependent variable on Structural Equation Modeling (SEM) analysis. The result will then be analyzed with SPSS 20.0 and AMOS 21.0 programs for Windows. The result of factor analysis showed that from 20 indicators, 4 factor is formed which is represent those 20 indicators. Those four factors are Work System Factor, Process Efficiency Factor, Work Readiness Factor, Technology and Management Support Factors. Those four factors obtained based on eigenvalues greater than one, so that the factors can represent several indicator that exist. These formed factors then developed with Structural Equation Modeling (SEM) analysis to determine the causality relationship to Performance Variables. The results of SEM analysis showed that Work System Factor, Process Efficiency Factor and Work Readiness Factor has positive and significant impact on performance variables, whereas Technology and Management Support Factor has no impact and not significant. Based on the result of the analysis, the company can now focus on increasing Work System Factor, Process Efficiency Factor and Work Readiness Factor for improving their performance.